Absorption, attenuation, scattering and backscattering inline data from the Gulf of Alaska in July 2020 - Benjamin Lowin; William J Burt (PANGAEA, 2023)
The following data set contains particulate absorption, particulate attenuation, and particulate backscatter data from an optical inline system. Auxiliary data from the R/V Sikuliaq extquotesingles existing underway system has also been attached, this includes standard shipboard physical oceanographic and meteorological data. The data was collected continuously during the cruises following previous work by the authors and IOCCG protocols (Burt et al., 2018 and IOCCG, 2019). The data has been binned to one-minute intervals to match with the existing underway data. The data was collected in the Northern Gulf of Alaska (NGA), as part of the expansion of the Long-Term Ecological Research (LTER) program in the Gulf. The data was collected using an ACS and BB3-eco triplet, on cruise SKQ202010s in the NGA.